Building Capacity in Psychiatric–Mental Health Nursing: Evidence-Based Strategies Across Four Domains - Erica Skarda Ramey (Journal of Psychosocial Nursing and Mental Health Services, 2026)
Purpose: The current narrative review synthesizes evidence on human capacity across emotional, cognitive, physical, and relational domains, providing psychiatric–mental health nurses (PMHNs) with evidence-based strategies to foster patient resilience and workforce sustainability. Capacity depletion affects patients and nurses, yet traditional assumptions that capacity restores naturally with time are contradicted by research. Method: CINAHL, PsycINFO, PubMed/MEDLINE, and Scopus were searched for studies published from 2005 to 2025 on capacity-building interventions in psychiatric–mental health settings, using the Critical Appraisal Skills Programme and Joanna Briggs Institute quality appraisal tools. Results: Mindfulness-based interventions, cognitive remediation therapy, progressive exercise programs, and peer support models produce measurable improvements across all domains. Conclusion: PMHNs can integrate assessment tools (e.g., Patient Health Questionnaire-9, Montreal Cognitive Assessment, 6-Minute Walk Test, UCLA Loneliness Scale), dose-specific interventions, and outcome tracking to systematically address capacity deficits while applying similar strategies to mitigate burnout and enhance professional resilience.